Modulation Immune Response of Thrush Disease infected Pigeons in Diyala Governorate - Hasan, Mohammed abdul hameeed; abood, Walaa Najm (Diyala Journal for Veterinary Sciences, 2023)
Candidiasis is the most frequent fungal infection in the oral cavity of pigeons. As a result, they have the potential to trigger an opportunistic infection known as oral candidiasis. This work aimed to isolate with Candida albicans from infected pigeon with thrush disease and the study of immunomodulatory effect. Candida albicans was isolated from oral mucosa and identifica-tion by using C.albicans elective agar. Blood sample was collected from infected pigeons and control from pigeon clinically don’t have any sign of candidiasis to apply for detection the level of IL-3, GM-CSF, and IL-25 by enzyme linked immunosorbent assay test. The following results were showed that Candida albicans was caused infection of Thrush disease at the percentage of (22.7%) from 22 isolate for the infected pigeon. C. albicans induced modulation in immune re-sponse through the effect in the levels of IL-3, GM-CSF, and IL-25. The conclusion was C. al-bicans caused thrush disease in pigeon that lead to the resulting in the immunomodulatory ef-fects.